Arrangement of Special Region in Corridor Dr. Mansyur (Talenta Publisher, 2020)
Medan is one of the largest cities in Indonesia after the metropolis of Jakarta also experienced strip development that has shown symptoms in the suburbs. The symptoms can identified from the aspect of land use on the outskirts of Medan in this case usually rural regions are characterized by agrarian areas switching functions to non-agrarian land, seen from the qualities of buildings in the suburbs, almost all buildings distinguished by urban or non-sectoral agrarian in a review of the building characteristics also added about the density of buildings and the number of buildings in a particular area. One of them is the problem that occurred in the corridor Dr. Mansyur. The original road capacity for calm residential traffic can no longer accommodate the dynamics of commercial activities. Traffic congestion, parking vandalism, pedestrian route malfunctioning by street vendors, the emergence of portable stands, and tent stalls on the edge of the road. The consideration will be based on predetermined variables, namely, elements of the city image, specifically paths, boundaries, regions, vertices, and landmarks. For this reason, mixed research carried out through observation and interviews and documentation studies. The results obtained from this study will show how the model of regional arrangement in anticipating the development strip of the city of Medan.